Biological and genetic characterization of Cryptosporidium spp. and Giardia duodenalis isolates from five hydrographical basins in northern Portugal - Almeida, André (2010)
To understand the situation of water contamination with Cryptosporidium spp. and Giardia spp. in the northern region of Portugal, we have established a long-term program aimed at pinpointing the sources of surface water and environmental contamination, working with the water-supply industry. Here, we describe the results obtained with raw water samples collected in rivers of the 5 hydrographical basins. A total of 283 samples were analyzed using the Method 1623 EPA, USA. Genetic characterization was performed by PCR and sequencing of genes 18S rRNA of Cryptosporidium spp. and b-giardin of Giardia spp. Infectious stages of the protozoa were detected in 72.8% (206 of 283) of the water samples, with 15.2% (43 of 283) positive for Giardia duodenalis cysts, 9.5% (27 of 283) positive for Cryptosporidium spp. oocysts, and 48.1% (136 of 283) samples positive for both parasites. The most common zoonotic species found were G. duodenalis assemblages A-I, A-II, B, and E genotypes, and Cryptosporidium parvum, Cryptosporidium andersoni, Cryptosporidium hominis, and Cryptosporidium muris. These results suggest that cryptosporidiosis and giardiasis are important public health issues in northern Portugal. To the authors’ knowledge, this is the first report evaluating the concentration of environmental stages of Cryptosporidium and Giardia in raw water samples in the northern region of Portugal.